Analisis Usabilitas Sistem Informasi Manajemen Penerimaan Koleksi Deposit Di Perpusnas Berdasarkan Pendekatan Evaluasi Heuristik - Suci Indrawati Irwan; Imas Sukaesih Sitanggang; Badollahi Mustafa (Jurnal Pustakawan Indonesia, 2015)
Acquisition Management of  Deposit Collection Information System in Indonesia National Library has been used for 3 years (since January 2012). During the usage, the Group of Acquisition, Monitoring, and Evaluation of Deposit Sub Directorate  found some obstacles include the unability of the system to detect double regist, a monotone display, too many menus and too many pages to get through before going to the desired page, the information resulted is not according to what needed, and the exsistance of backward analysis system which should be passed by a system when it has already been used. The data collection of this research used quessionaires which were spread among 17 system users that are the members Group of Acquisition, Monitoring, and Evaluation of Deposit Sub Directorate.  The data analysis used student statistic examination of one sample. The result of the study was the need of improvement about SIM of Deposit Collection Acquisition of Indonesia National Library related to the usability of the system to fulfill the usability elements, and the repairment recommendation belong to the categories of: Learnability, improvement of response for fasten of data searching by query optimization involving related tables of data required and indexing based on the tag ID and repair on the arranging and the use of features to be adjusted with the needs of users based on their user ID and position authority. Efficiency, improvement of response for fasten the response of data searching by query optimization involving related tables of data required and indexing based on the tag ID and addition to be able to copy and modify existing data and increase the ability of the system that the function keys in the keyboard  can be use in using the system. Easy to remember, the addition of the ability of the system that the keyboard function keys can be use in using the system. Error prevention, repair system's ability to identify errors and provide a message box or sign acclamation sign of error message containing an error message when the user made a mistake and adding dictionary menu associated with the terminology in the search box to avoid mistakes in typing. Satisfying, adding help menu that can provide guidance and can be followed when finding problem that help users to solve a problemKeywords : Heuristic Evaluation, Management Information System, Usability